2020
DOI: 10.1002/jmv.26518
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of death with severe fever and thrombocytopenia syndrome: A meta‐analysis and systematic review

Abstract: Severe hemorrhagic fever disease is caused by severe fever with thrombocytopenia syndrome virus (SFTSV) infection, which belongs to the Phlebovirus genus in the Bunyaviridae family. A comprehensive literature search of PubMed, Web of Science, Embase, Cochrane Library, Chinese National Knowledge Infrastructure databases, Wan Fang Data, Sinomed Database, and VIP database was conducted for articles which have described the clinical manifestation of deceased patients. Data from selected studies were pooled by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The results of routine blood tests failed in consistency intensively according to previous published papers [ 6 , 7 , 9 ]. This discrepancy can be primarily attributed to the differences of sample sizes and study regions.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The results of routine blood tests failed in consistency intensively according to previous published papers [ 6 , 7 , 9 ]. This discrepancy can be primarily attributed to the differences of sample sizes and study regions.…”
Section: Discussionmentioning
confidence: 84%
“…Liu MM et al found that old age, central nervous system manifestations, bleeding tendency, elevated serum enzymes and high vial load were risk factors for fatality among SFTS patients [ 6 ]. Wang X et al found that there were some significant differences between the nonfatal and fatal groups, such as headache, fatigue, diarrhea, vomiting and arrhythmia [ 7 ]. Dualis et al emphasized the importance of delay in hospital admission, high viral load, older age and presence of comorbid or complications on risk of dying of SFTS cases [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the association between male and adverse outcomes, including mortality, do not consistently exhibit, which differed across studies (Jung et al, 2019;Wang et al, 2020). More intriguingly, the risk factors that are known to change with sex and age are often interacted, which likely explain the sex differences observed for the mortality risk.…”
Section: Introductionmentioning
confidence: 93%
“…It is currently unclear whether neurons can be infected by SFTSV or viruses harboring SFTSV glycoproteins. Neurologic symptoms have been observed in human SFTS cases, but it remains unclear whether the SFTSV glycoproteins can initiate entry into neurons in vivo (52). To test the neuropathogenic potential of rVSV-SFTSV, we injected escalating doses of rVSV-SFTSV or VSV Indiana strain intracranially into the right cerebral hemisphere of 4-weekold C57BL/6 mice and observed the mice for 14 days.…”
Section: Rvsv-sftsv Is Attenuated In Ifnar -/Mice and Exhibits A Favorable Safety Profilementioning
confidence: 99%